TP53 oncogenic variants as prognostic factors in individuals with glioblastoma: a systematic review and meta-analysis - Esperante, Diego; Galicia, Kena Daza; Rivas-Cuervo, Kalu Gabriel; Cacho-Díaz, Bernardo; Trejo-Becerril, Catalina; Taja-Chayeb, Lucia; Aboud, Orwa; Carlos-Escalante, José Alberto; Wegman-Ostrosky, Talia (Frontiers in Neurology, 2024)
BackgroundThis systematic review and meta-analysis investigated the relationship between somatic TP53 oncogenic variants and prognosis, specifically with overall survival (OS) and progression-free survival (PFS) in patients diagnosed with supratentorial glioblastoma.MethodsWe included longitudinal studies and clinical trials involving a minimum of 40 adult participants diagnosed with supratentorial glioblastoma, wherein the status of TP53 variants was assessed. We conducted searches in multiple databases. We assessed bias risk using a modified version of the Quality in Prognosis Studies tool, and the certainty of evidence was evaluated following the principles of the GRADE approach.Results and conclusionThis study encompassed 23 papers involving 2,555 patients, out of which 716 had reported oncogenic variants. TP53 oncogenic variants were associated with a reduced likelihood of 1-year survival (OR 0.52, 95% CI 0.29–0.94). However, our analysis did not reveal any significant impact of TP53 variants on overall survival, progression-free survival, or 2-year survival. Therefore, this comprehensive analysis demonstrates that the presence of genetic variants in TP53 does not provide useful information for the prognosis of glioblastoma.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021289496.